The Quality of English writing in two Philippine news websites www.inquirer.net and www.gmanews.tv - Federico, Hazel Sarah Del Rosario
"This study examines the quality of writing in two Philippine news websites: www.inquirer.net and www.gmanews.tv. The internet has made possible the real time delivery of the news and has empowered audiences worldwide to get their dose of news wherever and whenever they want. While this has revolutionized the landscape of journalism, it has also increased the pressure for journalists to write stories faster than ever. To determine whether this fast-paced delivery of news is affecting the quality of writing in these websites, the researchers used both the quantitative and qualitative research methods. Two hundred forty articles from each website were selected and critiqued to determine the quality of writing in each website were interviewed. The researchers found the quality of writing in www.inquirer.net to be much better than that of www.gmanews.tv's as the former contained fewer mistakes."